Utilization of services under Janani Shishu Suraksha Karyakram for institutional deliveries in the public sector facilities, Sirmaur District, Himachal Pradesh, India - Uvi Tyagi; Kamaraj Pattabi; Prabhdeep Kaur (Wolters Kluwer Medknow Publications, 2016)
Background: Janani Shishu Suraksha Karyakram (JSSK) was initiated in 2011 to reduce the out of pocket expenditure for pregnant women. We estimated the proportion of mothers who received JSSK benefits and out of pocket expenditure (OOP) if any in Sirmaur, Himachal Pradesh. Materials and Methods: We did cross sectional survey in public sector facilities among 156 consecutive mothers using structured questionnaire. We computed the proportion of mother who received the benefits and the median OOP expenditure. Results: Among 156 mothers surveyed, 93 (60%) received the full benefits during hospital stay and 29 (19%) received full transport benefits. Free diagnostics and drugs were given to 149 (96%) and 134 (86%) respectively. Overall, 63 (40%) had median OOP Rs 210 during hospitalization and 127 (81%) had median OOP of Rs 420 during transport. Conclusion: JSSK benefitted the mothers utilizing the public sector facilities however drugs, consumables and transport contributed to the OOP expenditure.